THE IMPACT OF COMMUNICATION EFFECTIVENESS ON EMPLOYEE PERFORMANCE IN A PUBLIC SECTOR HUMAN RESOURCES DEVELOPMENT AGENCY - Lady Angelien; Andi Anto Patak; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This study examines the effectiveness of internal communication and its impact on employee performance within the Competency Certification and Institutional Division of the Human Resources Development Agency (BPSDM) of South Sulawesi Province. Using a qualitative approach with thematic analysis, data were collected through interviews, observations, and document analysis. The findings highlight that clear, transparent, and consistent communication enhances employee motivation, engagement, and performance. Effective communication reduces misunderstandings, improves team coordination, and fosters innovation. An inclusive culture and open leadership also play key roles in creating a supportive work environment. The study suggests that improving internal communication in government organizations like BPSDM can lead to better outcomes, operational efficiency, and productivity. These insights offer guidance for designing more effective communication strategies and fostering a more engaged workforce.